AutoLens: automated modeling of a strong lens's light, mass and source - Nightingale, James J.N. (2016)
The intricate analysis of a strong gravitational lens is a complex and computationally demanding problem, requiring the lensed source galaxy's extended light profile to be reconstructed simultaneously with non-linear modeling of the lens galaxy's mass and light. When successful, this analysis gives unrivaled insight into dark matter, cosmology and the most distant Universe. However, such studies remain resigned to small samples, simply due to how long this involved analysis takes. To address this, this thesis presents AutoLens, the first automated framework for comprehensive modeling of a strong gravitational lens's light, mass and source.